A review of molecular genetic markers and analytical approaches that have been used for delimiting marine mammal subspecies and species. (June 2017) - Rosel, Patricia E.; Taylor, Barbara L.; Hancock‐Hanser, Brittany L.; Morin, Phillip A.; Archer, Frederick I.; Lang, Aimee R.; Mesnick, Sarah L.; Pease, Victoria L.; Perrin, William F.; Robertson, Kelly M.; Leslie, Matthew S.; Berta, Annalisa; et al.
Abstract: Uncertainty in marine mammal taxonomy is increasingly being addressed using molecular genetic data. We examined 32 peer‐reviewed articles published between 1994 and 2011to review methodological practices, consistency of markers and analytical methods, and overall quality of arguments used when genetic data have been employed to delimit new species and subspecies of marine mammals. The mitochondrial DNA (mtDNA) control region was the primary genetic marker used in these studies, but analytical methods varied greatly across studies. Diagnosability, a common metric for delimiting subspecies with morphological data, was only used through citing of fixed differences in mtDNA sequences. Assignment tests based on microsatellite data were less common but were applied at both taxonomic levels. Nuclear DNA sequence data were rarely used. Basic background material needed to evaluate the strength of arguments, such as distribution and sampling maps, were often missing. For most studies, sample sizes were good, but adequate geographic sampling for broadly distributed taxa was often lacking, diminishing the strength of evidence for taxonomic distinctness. Examining these empirical cases revealed a mixture of sound and inadequate practices for genetic studies of cetacean taxonomy and suggested that improvements could be made to the field by developing standard guidelines.